2018
DOI: 10.1177/0305735617746734
|View full text |Cite
|
Sign up to set email alerts
|

First and foreign language early reading abilities: The influence of musical perception

Abstract: There is a growing body of literature that recognises how music perception affects first-language learning, but much less is known about its influence on foreign-language reading skills. The purpose of this paper is to examine the effect of music perception abilities on the acquisition of some foreign early reading skills based on their transference from first language. Data for this study were collected from 63 Spanish-speaking English-language learners studying second grade of primary school. We used a music… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…To some extent, we expected that the correlational study could yield positive results. Earlier studies had already reported the positive correlations between reading skills in L1 and second languages (Koda, 2007a;Gómez-Domínguez et al, 2019), or between phonological awareness and reading components such as fluency (van den Boer et al, 2014;Flaugnacco et al, 2015), but we decided to check it again to present our model. The SEM, as a statistical-causal method, allowed us to analyze how variables would behave after previously observed correlations, according to an a priori hypothesized model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To some extent, we expected that the correlational study could yield positive results. Earlier studies had already reported the positive correlations between reading skills in L1 and second languages (Koda, 2007a;Gómez-Domínguez et al, 2019), or between phonological awareness and reading components such as fluency (van den Boer et al, 2014;Flaugnacco et al, 2015), but we decided to check it again to present our model. The SEM, as a statistical-causal method, allowed us to analyze how variables would behave after previously observed correlations, according to an a priori hypothesized model.…”
Section: Discussionmentioning
confidence: 99%
“…Studies about musical aptitude and "seemingly" visual reading skills such as silent reading fluency, remain to be scarce and inconclusive (Zeromskaite, 2014;Gordon et al, 2015), especially with adult readers who learn a language in a foreign context (Swaminathan et al, 2018). Gómez-Domínguez et al (2019) provided insights into how music perception affects early reading skills in 63 Spanish children learning English. Their findings support a transfer of music perception abilities to L1 young learners' reading abilities that affect the alphabetic principle, the phonemic awareness and the word recognition skills in their FL early reading skills.…”
Section: Introductionmentioning
confidence: 99%
“…Although studies directly investigating the link between musical skills and foreign language reading skills in adults are scarce, a general picture emerges, that musical aptitude usually tested in children's L1 reading skills (Degé et al, 2015;Gordon et al, 2015;Strait et al, 2011) also impacts on children's (Gómez-Dominguez et al, 2019) and on adults' foreign reading fluency skills (Foncubierta et al, 2020) even when the foreign language does not belong to the same Indo European stock, as it is the case of this study. Data obtained from the musical aptitude test corroborate and cross-validate learners' self-reported musical training data.…”
Section: Discussionmentioning
confidence: 59%
“…The term musical aptitude is usually defined from two different points of view. Gómez-Domínguez et al (2018) quote Levinson for the nurturing perspective and Trehub for the nativist perspective. In fact, Foncubierta, Machancoses, Buyse and Fonseca.Mora (2020) define musical aptitude as a range of inherent abilities for music that an individual is born with and that are possibly shaped by informal exposition to music.…”
Section: Concept Of Musical Aptitude Musicality and Phonological Awar...mentioning
confidence: 99%